Combinatorial Performance Mapping of Near-NMC111 Li-ion Cathodes - Daniel Commandeur; Christian Sabado; Thomas E. Ashton; Jawwad A. Darr (Journal of Materiomics, 2022)
A combinatorial library of twenty-three, phase pure, near-NMC111 (LiNi0·33Mn0·33Co0·33O2) compositions were synthesised and their electrochemical performance, was mapped (in lithium ion half-cells). Each of the 23 compositions was made in series, using a two-step process of 1) a rapid initial continuous hydrothermal precipitation, followed by 2) solid state lithiation. The 23 lithiated NMC samples were then subjected to analytical methods including electron microscopy (selected samples), Powder X-ray Diffraction and electrochemical tests in half cell Li-ion configurations versus Li metal. A sample with a Ni:Mn:Co (NMC) ratio of 39:28:33, revealed a specific capacity of 150 mA h g−1 at a C/20 rate, which was 63 and 43% greater capacity than NMC111 and NMC433 samples produced in this work, respectively. The sample with NMC ratio 47:25:28, showed the best capacity retention characteristics, retaining 70% of its C/20 capacity at 1C, after 40 cycles. Further analysis of all the samples by cyclic voltammetry and electrochemical impedance spectroscopy, allowed compositional mapping of diffusion coefficients. Overall, the mapping data revealed a gradual change of properties across compositional space, which has validated our combinatorial approach and allowed identification of the optimum performing near-NMC111 cathode materials.